Gender Mainstreaming Dalam Kurikulum Mata Kuliah Agama Islam di PTN & PTS di Yogyakarta - Suryadilaga, Muhammad Alfatih; Yusuf, M.; Rofiq, Ahmad (Musawa Jurnal Studi Gender dan Islam, 2008)
Equality for women is a fundamental problem in education. There is, in fact, a gap between women and men. The Department of National Education of Indonesia, therefore, makes an effort to decrease the gap through what so-coll gender mainstreaming. This article is to investigate gender mainstreaming program in higher educational Institutions, particularly in Yogyakarta. To have an adequate picture of gender mainstreaming program, UGM and UNY are selected to represent the state higher educational Institutions, while UII and UPN are as the sample of the private ones. The subject matter of Islamic religion is elected due to its contents that still include gender bias. The reality indicates that the available curriculum of Islamic religion in both State Islamic Higher Education and Private Higher education is not inclusive gender yet, in terms of contents, illustrations or sentences used to explain the contents. The model of learning and teaching, more over, is also still not responsive gender, particularly because the teachers or lecturers who deliver the subject have no gender perspective or sensitivity, although they have deep understanding of Islamic spirit that promotes gender equality.